AN ANALYSIS OF ENGLISH AS A FOREIGN LANGUAGE (ELF) STUDENTS SPEAKING PROBLEMS AT TWELVE GRADES OF SMA SWASTA DHARMA KARYA BERINGIN IN THE ACADEMIC YEAR 2024/2025 - Tampubolon, Sahlan; Lisyeni Verentia, Cleydia; Siahaan, Sahat Taruli (English Language Teaching Prima Journal (ELT), 2024)
This research delves into the speaking challenges faced by English as a Foreign Language (EFL) students at SMA Swasta Dharma Karya Beringin in the academic year 2024/2025, aiming to provide a comprehensive understanding of the linguistic and psychological obstacles hindering students' proficiency in spoken English. By integrating psycholinguistic and language learning theories, the study explores how psychological factors and effective language acquisition strategies influence language learning processes. Through interviews and tests with twelfth-grade students, the research focuses on identifying specific challenges in linguistic discourse engagement and investigating factors contributing to these difficulties, such as fear of mistakes, shyness, and language proficiency issues. The study aims to offer recommendations to enhance students' speaking abilities, contributing to a nuanced understanding of language acquisition and psychological aspects in the educational context, with the ultimate goal of improving EFL students' speaking skills at SMA Swasta Dharma Karya Beringin.